Internship experience as a feature journalist from magazine desk of Daily Sun - Bhuiyan, MD. Ashiquer Rahman (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.